Diagnosis Gangguan Autisme Pada Anak Menggunakan Metode Certainty factor dan Lokasi Terapi Autisme di Kota Bengkulu - Rima Yanti Nasution, Nofa; Andreswari, Desi; Coastera, Funny Farady (Jurnal Pseudocode, 2024)
Autism is a developmental disorder that affects children with symptoms of disturbances and delays in cognition, language, behavior, communication and social interactions. Bad stigma and lack of information related to autism and the location of autism therapy are also obstacles in society. To help overcome these obstacles, an expert system was created which aims to diagnose autism disorders in children and provide information about the location of autism therapy in Bengkulu City. The system developed uses the certainty factor method, with functionality testing success of 100% and certainty factor accuracy testing using 25 test case data of 100%. Keywords: Autism, Certainty Factor, Diagnosis, Location of Therapy